1986
DOI: 10.1161/01.str.17.2.179
|View full text |Cite
|
Sign up to set email alerts
|

Hemorrhagic cerebral infarction--a prospective study.

Abstract: SUMMARY In 65 cases of ischemic cerebral infarction, CT scans and quantitative assessments of the neurological disturbances were undertaken at specific intervals during the 4 week period after stroke. Forty-three patients underwent lumbar puncture to determine the serum/CSF albumin ratio. The etiology of the infarction was evaluated on the basis of angiographic, ultrasonic and cardiologic findings. A hemorrhagic transformation of the infarction occurred in 28 patients, eleven within the first week, and 15 with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
140
1
5

Year Published

1987
1987
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 307 publications
(165 citation statements)
references
References 28 publications
14
140
1
5
Order By: Relevance
“…16 In addition, reperfusion of ischemic brain tissue after thrombolytic therapy may involve the risk of reperfusion injury through enhanced formation of reactive oxygen species and metalloproteinase activation. 18,24 In the present study, all cases of contrast enhancement and 86% of the contrast extravasation developed in the basal ganglia. Komiyama et al 8 reported 2 cases of extravasation of contrast medium that occurred in the region of the basal ganglia.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…16 In addition, reperfusion of ischemic brain tissue after thrombolytic therapy may involve the risk of reperfusion injury through enhanced formation of reactive oxygen species and metalloproteinase activation. 18,24 In the present study, all cases of contrast enhancement and 86% of the contrast extravasation developed in the basal ganglia. Komiyama et al 8 reported 2 cases of extravasation of contrast medium that occurred in the region of the basal ganglia.…”
Section: Discussionsupporting
confidence: 56%
“…15,16 It is well known that contrast enhancement of brain tissue on CT or MR is caused by leakage of contrast medium from vessels into the extracellular spaces as a result of increased permeability of the BBB. 17,18 Contrast enhancement of brain tissue on nonenhanced CT scans taken immediately after intra-arterial thrombolysis may occur over a prolonged period, with contrast leaking through the BBB of the microvessels supplying the basal ganglia during thrombolysis. When intra-arterial thrombolysis is performed, multiple angiographic injections of contrast medium through either a guiding catheter or a microcatheter is done around the lenticulostriate arteries to assess the response of thrombolytic therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Hornig et al evaluated 65 patients' data. They detected HT with brain CT in 28 cases, 40% in the first week, and the rest 60% in the second post-stroke week [16]. These earlier reports show how difficult it is to define the most appropriate time for the diagnosis of HT.…”
Section: Discussionmentioning
confidence: 95%
“…Previous studies have focused on the possible aetiological role of the following parameters: age [8,10,11,13,14], systolic and diastolic arterial blood pressure [14,15], congestive heart failure [11], body temperature [15], serum glucose level [8,14], treatment with anticoagulants [10,15], pre-treatment with aspirin [10,11], early ischaemic signs on CT [11,13,15], mean infarct volume [10,11,15], plasma matrix metalloproteinase-9 [15]. The adequate time window for detection of haemorrhagic transformation is also disputed [16] and autopsy is the method which provides the most accurate diagnosis in stroke. Our goals were to i) analyse the correlation between clinical and neuropathological diagnosis; ii) to assess the clinically undisclosed findings revealed with the neuropathological analysis in a series of consecutive cases reflecting the routine practice of a stroke centre, iii) to emphasize the importance of the neuropathological evaluation in establishing the real frequency of haemorrhagic transformation which may warrant modifications of stroke protocols and diagnosing clinically undetected brain diseases.…”
Section: U N C O R R E C T E D P R O O Fmentioning
confidence: 99%
“…Open doseranging studies include the NIH tPA Study (Brott et al, 1990) Haemorrhagic transformation is a potential complication of thrombolytic treatment. This must be viewed in the light of the natural incidence of haemorrhagic transformation, which ranges from 10-43% depending on the circumstances and which increases as the time elapsed from stroke progresses (Fisher et al, 1984;Hornig et al, 1986;Lodder, 1984;Okada et al, 1989). The rate of intracerebral haemorrhage in 46,092 patients with myocardial infarction who were randomised in the ISIS-3 trial was only 0.3-0.7%, streptokinase causing significantly less haemorrhage than tPA or APSAC.…”
Section: Haemodynamic and Vascular Mechanismsmentioning
confidence: 99%